2017
DOI: 10.1051/epjconf/201713801008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperons polarization in heavy-ion collisions

Abstract: Abstract. We study the structure of vorticity and hydrodynamic helicity fields in peripheral heavy-ion collisions using the kinetic Quark-Gluon Strings Model. The angular momentum which is a source of P-odd observables is preserved within this model with a good accuracy. We observe the formation of specific toroidal structures of vorticity field. Their existence is mirrored in the polarization of hyperons of the percent order. The observed qualitative energy dependence of polarization was predicted earlier and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…It was concluded that the observed rotational fluid has the largest vorticity, of the order of ∼10 22 s −1 , that ever existed in the universe. The measured polarization quantitatively agrees with the hydrodynamic [5,6] and kinetic [7][8][9][10] model calculations.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…It was concluded that the observed rotational fluid has the largest vorticity, of the order of ∼10 22 s −1 , that ever existed in the universe. The measured polarization quantitatively agrees with the hydrodynamic [5,6] and kinetic [7][8][9][10] model calculations.…”
Section: Introductionsupporting
confidence: 77%
“…This enhancement at peripheral rapidities was illustrated in Ref. [8] at the example of Au+Au colli- * e-mail: Y.Ivanov@gsi.de sion at √ s N N = 5 GeV. Although not all models predict the polarization minimum at the midrapidity [14].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation